Aminas bioativas e atividade antioxidante em cogumelos - Guilherme Coelho Lopes dos Reis (2014)
The objective of this study was to investigate the levels of bioactive amines, phenolics, the antioxidant activity and the existence of correlation between antioxidant activity and the levels of polyamines and phenolics in eight types of edible mushrooms available in Belo Horizonte, MG, Brasil. The amines were determined by ion-par high-performance liquid chromatography. The antioxidant capacity was investigated by the methods of inactivation of radical DPPH, ion reduction Mo (VI) and acceleration of lipid oxidation by Rancimat. The levels of total phenolics in mushrooms were determined by Folin Ciocateau reaction. The amines spermidine, putrescine, cadaverine, agmatine, tyramine, tryptamine and phenethylamine were detected in the samples. Spermidine was present in large quantities in every mushroom. The highest content of spermidine was found in Shimeji Preto (1366.7 mg/kg dry mass). Agmatine was detected in six of the eight types of mushrooms analyzed, and the highest content was found in Salmão (2205.9 mg/kg dry mass). All mushrooms showed low levels of biogenic amines. The phenolic contents ranged from 6.15 to 11.74 mg EAG/g of mushroom (dry mass). Shimeji Preto showed the highest total phenolics. The metanolic extract of most mushrooms showed antioxidant activity in all the antioxidant methods evaluated. Only Shitake and Eryngii did not have antioxidant activity by Rancimat. There was no predominance of a particular mushroom in the antioxidant tests. There was no significant correlation between results for the antioxidant methods. Strong correlation of the levels of spermidine in mushrooms and the results of DPPH inhibition was observated. There was a moderate correlation of the levels of spermidine with phenolic contents.